The Use of English Media Containing Animal Information in Serulingmas Banjarnegara Interactive Zoo - Azzahra, Firda Aurina; Sari, Rosdiana Puspita (Jurnal Vokasia, 2022)
In every zoo, there must always be informed, especially about animals. This information is very important because it is a source of knowledge for visitors who travel to a zoo. Serulingmas has 47 animals which are grouped into 20 mammals, 20 aves, and 7 reptiles. The information of the animals are written in Bahasa Indonesia. The purposes of this article are toexplain the process in creating animals information in English for Serulingmas Banjarnegara Interactive Zoo and to know the obstacle and solution in creating animals information in Serulingmas Banjarnegara Interactive Zoo. The methods used are observation, documentation, and producing practice.